"Adaptivnaja fiziceskaja aktivnost" kak novaja disciplina v cemejstve sportivnych nauk - Ozolina, E. V.; Dimitriyev, V. S.; Rubtsova, N. O. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
This article is devoted to a new scientific problem and the educational discipline - "adapted physical activity". The authors consider the general states of these problems, analyze the adapted physical activity as a profession, as an educational discipline, and as the independent area of a knowledge, interacting with the overlapping sciences. They substantiate the strategy of researches in the area of the adapted physical activity.